Kegiatan Penyuluhan Kesehatan pada Pasien Pre Anestesi untuk Mengurangi Kejadian Mual Muntah - M. Hafiduddini; Prayitno Prayitno (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
Health education before anesthesia is a vital strategy in minimizing the risk of side effects, such as nausea and vomiting, which are common after surgery. These side effects can significantly affect patient comfort and recovery time. This community service activity aims to improve patient understanding of the necessary pre-anesthesia preparation steps to reduce the incidence of these postoperative complications. The method utilized in this study is a quantitative approach, employing a pre-experimental one-group pre-test and post-test design. A total of 20 respondents, all patients who underwent surgery with anesthesia at PKU Muhammadiyah Karanganyar Hospital, participated in the study. Prior to the educational intervention, patients completed a pre-test to assess their baseline knowledge about anesthesia preparation. After receiving the educational session, which included detailed explanations of anesthesia procedures and the importance of pre-anesthesia preparation, patients were given a post-test. The results of the community service demonstrated a significant improvement in the understanding of patients regarding the preparation for anesthesia. This improvement was evidenced by a noticeable difference in pre-test and post-test scores. The findings highlight the effectiveness of education in enhancing patient awareness and potentially reducing the occurrence of side effects such as nausea and vomiting post-surgery. Therefore, the implementation of pre-anesthesia education should be considered an essential practice to improve patient outcomes and support safer surgical experiences.